Exploring the Landscape of HPV Vaccine Acceptability in Pakistan: A Systematic Review - Ali, Parniya Akbar; Khalid, Samina Naeem; Memon, Areeba; Khan, Sabine; Noreen, Khola; Tariq, Muhammad Abdullah (Journal of Rawalpindi Medical College, 2025)
The FDA-approved vaccination against the Human Papillomavirus (HPV) was introduced in 2006, and since then, many countries have successfully implemented various HPV immunization programs. However, Pakistan, with approximately 73.8 million women at risk of cervical cancer, significantly lags behind, and currently, the HPV vaccination is not included in any immunization programs. This could be attributable to a dearth of awareness and knowledge amongst the masses regarding the HPV vaccine. The primary aim of this review was to evaluate public awareness and acceptance of the HPV vaccine in Pakistan. A literature search was conducted using electronic databases, including PubMed, Google Scholar, and ScienceDirect. Of the 222 studies in total, 15 were finalized, which met the review’s criteria and objectives. The review assessed the population’s awareness of the HPV vaccine’s availability, their current vaccination status against HPV, and their willingness to get vaccinated against HPV. The analysis revealed that the current immunization status remains alarmingly low, which could be in line with low awareness regarding the availability of the HPV vaccine in Pakistan. There is a pressing need to introduce the HPV vaccination into the national immunization schedules and simultaneously strengthen regulatory frameworks surrounding the HPV vaccination in Pakistan. Key words: Human Papillomavirus; HPV vaccine; Immunization programs; EPI; Pakistan